High risk factors of diabetic foot and related nursing interventions (糖尿病足的高危因素分析及护理干预现状) - JI Congying (季聪颖) (中西医结合护理)
The diabetic foot is one of the severe complications in diabetic patients. It's also a major cause of disability and death. This paper summarized and outlined the risk factors, prevention points and nursing interventions for diabetic foot by literature review, in order to improve the quality of life of diabetic patients, enhance clinical care, and prevent the occurrence of diabetic foot. (糖尿病足(DF)是糖尿病患者严重并发症之一, 是糖尿病患者致残、致死的主要原因之一。本研究通过查阅文献, 归纳概括目前DF的高危因素、预防要点及护理干预现状, 旨在为预防DF、提高糖尿病患者生活的质量提供参考。)